Kualitas Pelayanan Pembuatan dan Pencatatan Akta Kelahiran di Dinas Kependudukan Sipil Kota Medan - Lubis, Marwah Aini; Sembiring, Walid Mustafa; Wulandari, Novita (Mahesa Research Center, 2025)
This study aims to evaluate the quality of birth certificate preparation services at the Medan City Population and Civil Registration Office (Disdukcapil) by identifying factors that affect the quality of these services. Using a descriptive qualitative approach, this study involved 10 employees of the Disdukcapil and 15 community users of the service as respondents. Data were collected through in-depth interviews, observations, and documentation studies. This research adopts Zeithaml's theory of service quality, which includes five dimensions: tangible (physical evidence), reliability (reliability), responsiveness (responsiveness, assurance (guarantee), and empathy. The results of the study show that the Medan City Disdukcapil has provided good service in several dimensions, such as the cleanliness of the waiting room and the responsiveness of officers. However, there are still shortcomings in the reliability dimension related to inaccuracy in data filling, as well as a lack of clear information about management procedures. This research recommends increasing human resource capacity, providing better information facilities, and developing more efficient technology systems to improve service quality.